Model Pemerkasaan Politik Perempuan di Wilayah Konflik Aceh - Sabirin; Zalikha; Chairawati, Fajri (Advances in Humanities and Contemporary Studies, 2020)
The model of political empowerment in building women's awareness of their political rights has been carried out in various places, but the application of the model of women's political empowerment in the conflict areas has not yet been maximized. This is due to the tradition of political education among women in the conflict has not been implemented. Cultural faktor that do not involve women's participation in the political aspect continue to this day, at least in Aceh. This study is an academic response to a number of phenomena that limit the involvement of women in filling seats in the legislature, both in the Regency and Province. This qualitative based on 5 informants to find information about women's political participation through observation, interviews and participants. Based on the field study, it was found that 20 women who fail to be members of the legislature because do not understanding the political procedures in accordance with the regulations in the conflict area. No special academic participation has been found in empowering women's politics. Not yet found the participation of ulama in empowering women's politics in conflict areas, especially Aceh. According to the author's analysis, this is an important skill to increase women's political awareness in conflict areas. The results of this study can be used by all parties who are interested in increasing women's political participation in conflict areas.